Digital leadership and employee innovative performance: the role of job crafting and person–job fit - Yongkang Wang; Jonghyuk Park; Qi Gao (Frontiers in Psychology)
With the development of the digital economy and digital technology, innovation-driven growth has become the key to the digital transformation of various organizations. Employee behavior and digital leadership affect the innovative performance of a company significantly. Using the proactive motivation model, this study constructed a moderated mediation model with job crafting as the mediating variable and person–job fit as the moderating variable. Through statistical analysis of 306 valid questionnaires answered by employees in manufacturing firms, this study determined how digital leadership affects innovative performance by promoting employees to carry out job crafting. The study conducted structure equation modeling to examine the hypotheses. The findings indicate the following: (1) Digital leadership has a positive effect on employee innovative performance. (2) Two of the three job crafting strategies (task crafting and cognitive crafting) mediate the relationship between digital leadership and employee innovation performance. (3) Person–job fit positively moderates the relationship between cognitive crafting and employee innovation performance. (4) Person–job fit positively moderates the indirect effect of digital leadership on employee innovation performance through cognitive crafting.